2019
DOI: 10.1002/art.40788
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Longitudinal Surveillance of the IgG Autoantibody Repertoire in Established Systemic Lupus Erythematosus

Abstract: Objective. To investigate the role of epitope spreading in established systemic lupus erythematosus (SLE). Methods. IgG autoantibody reactivity with 398 distinct recombinant proteins was measured over a period of 6 years in 69 SLE patients and compared to that in 45 controls. Changes in mean fluorescence intensity (MFI), number of autoantibodies to distinct antigens, and reactivity with distinct clones of established antigenic targets (e.g., U1 RNP, Sm, and ribosomal P) representing epitope fine mapping were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Another consideration is the sampling time. Longitudinal prospective studies using certain biomarker panels could be applied in disease prevention, activity monitoring, as well as prognosis following treatments (105)(106)(107). Furthermore, additional large cohorts of samples should be collected to prove any novel discoveries.…”
Section: Bio-sample Collectionmentioning
confidence: 99%
“…Another consideration is the sampling time. Longitudinal prospective studies using certain biomarker panels could be applied in disease prevention, activity monitoring, as well as prognosis following treatments (105)(106)(107). Furthermore, additional large cohorts of samples should be collected to prove any novel discoveries.…”
Section: Bio-sample Collectionmentioning
confidence: 99%
“…Baseline serum blood samples of 411 patients from a multicenter national cohort of early arthritis (Course And Prognosis of Early Arthritis, CAPEA) [16] were obtained for a multiplex analysis of 390 autoantibodies to distinct proteins (supplementary table 1) by Luminex technology as described previously [17]. Inclusion criteria for the CAPEA study were age above 18 years with clinical arthritis for ≤ 26 weeks in 2 joints or ≥ 1 joint with morning stiffness ≥ 30 min.…”
Section: Patients and Clinical Datamentioning
confidence: 99%
“…IgG reactivities against 390 unmodified recombinant proteins and 390 corresponding in vitro citrullinated recombinant proteins were assessed: Luminex bead-based antigen arrays were used for the multiplex analysis of IgG autoantibody reactivity as previously described [17,18]. In total, 390 antigens were selected based on literature data, and autoantibody reactivity data identified in previous high-content profiling studies in rheumatoid arthritis and SLE [18,19].…”
Section: Multiplex Bead-based Autoantibody Detectionmentioning
confidence: 99%
“…Autoantibodies, such as anti-dsDNA antibodies and anti-Ro antibodies, are present many years before the diagnosis of SLE and progressively accumulate until clinical onset [108]. Recent analysis with multiplex bead-based antigen detection for 398 antigens, showed that the number of epitopes recognized by autoantibodies generally do not change over six years in established SLE patients [109]. dsDNA and histone H3 autoantibodies were notable exceptions and constituted disease activity markers.…”
Section: Immune Profiling Of Slementioning
confidence: 99%